"a birodalmi német gyermekeket […] Magyarország régi becses kultúrájában jártassá teszik” : a budapesti Németbirodalmi Iskola, 1908–1944 = “Teach the children of the German Empire […] about Hungary's old and distinguished culture" : The Budapest school of the German Empire, 1908–1944 - Orosz, László (Közép-Európai Közlemények, 2017)
The Budapest-based Reichsdeutsche Schule (School of the German Empire) was a popular and distinguished school during the interwar period. Originally founded as a school for the children of German citizens temporarily based in Hungary for business or diplomatic reasons, children of other nationalities were soon allowed to enroll, including Hungarian children from the beginning of the 1920’s. The school became extremely popular among the bourgeois families of Budapest, and the Jewish residents of the city also preferred sending their children there. The institution, which was characterized by its international atmosphere, tolerant spirit and complete lack of political extremism, taught its students European perspectives and ways of thinking, in addition to providing an acknowledged high quality Hungarian education. The numerous graduates who would go on to leave their mark in a variety of fi elds were a fi tting testament to the high educational standards of the school. The teaching staff consisted mainly of open-minded and tolerant pedagogues (according to later descriptions by students), so much so that when education reforms were introduced following Hitler’s transition to power, German teachers requested transfer to the Budapest-based school, where they would enjoy greater academic freedom and try to stay until better times. Moreover, they consciously sought to avoid acting and behaving as point men for the German Reich. Their treatment of Jewish students provided the best testimony to what degree their thinking did not conform to circumstances in Germany. On more than one occasion the school found itself in open confl ict with the leadership of Nazi Germany. For example, in 1944, on the heels of the German occupation of Hungary, the school bravely stood up in defense of its Jewish students (by administering matriculation exams early and by hiding students in the basement of the school building). Such conduct had contradicted the smear campaigns that occurred after WWII. The 2004 Hungarian Film Festival awarding-winning documentary fi lm about the school was a step in rehabilitating its reputation.